2017
DOI: 10.1038/s41598-017-18203-2
|View full text |Cite
|
Sign up to set email alerts
|

High-Temperature Requirement A1 (Htra1) - A Novel Regulator of Canonical Wnt Signaling

Abstract: Different cancer types as well as many other diseases are caused by aberrant activation of the canonical Wnt signal transduction pathway, and it is especially implicated in the development and progression of colorectal cancer (CRC). The main effector protein of the canonical Wnt signaling cascade is β-catenin, which binds to the T- cell factor/lymphoid enhancer factor (TCF/LEF) and triggers the activation of Wnt target genes. Here, we identify the serine protease High-Temperature Requirement A1 (HTRA1) as a no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 46 publications
2
27
0
Order By: Relevance
“…An XTT proliferation assay was used to evaluate the impact of the best peptide inhibitors of BTLA/HVEM complex formation on the proliferation of peripheral blood mononuclear cells. This assay is widely utilized in the measurement of a broad spectrum of biologically active compounds, in order to assess their impact on cell proliferation and, thus, indirectly, cell cytotoxicity [38,39]. The effect of gD(1-38)(L4C-R36C), gD(1-38)(L4C-V37C), and gD(1-36)(K10C-T29C) on cell proliferation, and indirectly cell cytotoxicity, was examined in PBMCs from healthy volunteers.…”
Section: Xtt Cell Proliferation Assaymentioning
confidence: 99%
“…An XTT proliferation assay was used to evaluate the impact of the best peptide inhibitors of BTLA/HVEM complex formation on the proliferation of peripheral blood mononuclear cells. This assay is widely utilized in the measurement of a broad spectrum of biologically active compounds, in order to assess their impact on cell proliferation and, thus, indirectly, cell cytotoxicity [38,39]. The effect of gD(1-38)(L4C-R36C), gD(1-38)(L4C-V37C), and gD(1-36)(K10C-T29C) on cell proliferation, and indirectly cell cytotoxicity, was examined in PBMCs from healthy volunteers.…”
Section: Xtt Cell Proliferation Assaymentioning
confidence: 99%
“…Interestingly, a recent study demonstrated thrombospondin-1 is a substrate for HtrA1, and proteolytically released fragment of thrombospondin-1 promotes tube formation by endothelial cells [91]. Moreover, independent of catalytic activity, secreted HtrA1 inhibits transforming growth factor (TGF)-β/BMP signaling pathways by interacting with their receptors and inhibit Wnt pathway by interacting with β-catenin [92].…”
Section: Degradation Of Divergent Ecm Proteinsmentioning
confidence: 99%
“…It has been documented that abnormal constitutive of several signaling pathways are implicated in tumorigenesis of CRC, especial Wnt/β‐catenin signaling (Globus et al, ). The Wnt/β‐catenin signaling is classified into canonical and non‐canonical pathways.…”
Section: Introductionmentioning
confidence: 99%